A highly enantioselective asymmetric Darzens reaction catalysed by proline based efficient organocatalysts for the synthesis of di- and tri-substituted epoxides. Issue 79 (20th September 2017) - Ashokkumar, Veeramanoharan; Siva, Ayyanar; Ramaswamy Chidambaram, R.
Abstract : A new class of proline based chiral organocatalysts was designed and efficient catalysts for asymmetric Darzens reaction to obtain active di- and tri-substituted epoxides with high yields (up to 97%) and excellent ee's (up to 99%) under mild reaction conditions. Abstract : A new class of easily available and readily tunable proline based chiral organocatalysts was found to efficiently catalyse an unprecedented highly enantioselective asymmetric Darzens reaction of α-chloroketones and substituted α-chloroketones with various aldehydes, which directly produces optically active di- and tri-substituted chiral epoxides with higher product yields (up to 97%) and excellent ee's (up to 99%) under mild reaction conditions.